(untitled) (Economic and Political Thought, 2024)
The article presents the European Union, especially its creation, evolution and significance for the integration and security of Europe in the period 1993–2024. In addition, it shows the EU’s prospects and its place in the emerging new international order. The author states that today it is difficult to imagine not only our continent, but the whole world without the EU. It is one of the main entities of contemporary international relations and, together with NATO, co‑creates the Euro‑Atlantic security system, which guarantees the maintenance of peace in Europe and in the world. It has contributed to the development of universal cooperation between the countries of our continent and has strengthened Europe’s position in the international arena.